Biological effect of microengineered grooved stents on strut healing: a randomised OCT-based comparative study in humans. Issue 1 (22nd May 2017) - Vesga, Boris; Hernandez, Hector; Higuera, Sergio; Gasior, Pawel; Echeveri, Dario; Delgado, Juan A; Dager, Antonio; Arana, Camilo; Simonton, Charles; Maehara, Akiko; Palmaz, Julio; Granada, Juan F
Abstract : Objective: To evaluate the biological effect of microengineered stent grooves (MSG) on early strut healing in humans by performing optical coherence tomography (OCT) analysis 3 weeks following the implantation. Background: In the experimental setting, MSG accelerate endothelial cell migration and reduce neointimal proliferation compared with bare metal stent (BMS). Methods: A total of 37 patients undergoing percutaneous coronary intervention with de novo coronary lesions were randomly assigned to either MSG (n=19) or an identical BMS controls (n=18). All patients underwent OCT imaging at 3 weeks. A total of 7959 struts were included in the final analysis. Results: At 3 weeks following stent implantation, almost all struts analysed (~97%) had evidence of tissue coverage. The percentage of partially covered struts was comparable between both groups. However, the percentage of fully embedded struts was higher in the BMS group (81.22%, 49.75–95.52) compared with the MSG group (74.21%, 58.85–86.38). The stent-level analysis demonstrated reduction in neointimal formation (neointimal hyperplasia area and volume reduction of ~14% and ~19%,  respectively) in the MSG versus the BMS group. In the strut-level analysis, an even greater reduction (~22% in neointimal thickness) was seen in the MSG group. Layered neointimal was present in ~6% of the OCT frames in the BMS group while it was not present in the MSG group. Conclusions: MSG induced a more homogeneous and predictable pattern of surface healing in the early stages following stent implantation. The biological effect of MSG on stent healing has the potential to improve the safety profile of current generation drug-eluting stents. Classifications: BMS, OCT, clinical trials.